Newton's Recurrance

If you start with a quadratic function f and with to find a root, start with any point x(0). Then recursivly define:

#begin Maple Code
interface(prettyprint=false):
f := (x) -> a*x^2 + b*x + c:
df := D(f):
x := proc(n)
  if n=0 then x0
  else simplify( x(n-1) - f(x(n-1)) / df(x(n-1)) )
  fi
end:
for n from 0 to 4 do printf("x(%a) = %q\n\n",n,x(n)) end do:
#end Maple Code

If x0 is chosen well, then x(n) will converge to a zero of f.

I let x(0) be the formal variable x0 and never plug in a value for it. x(n) is in the form of P(n,x0) / Q(n,x0). P and Q are interesting polynomials!

#begin Maple Code
# stolen from Jim Propp, via email.
P := proc(n) option remember;
  if n=0 then x0
  else simplify( a * P(n-1) * P(n-1) - c * Q(n-1) * Q(n-1) );
  fi;
end:
Q := proc(n) option remember;
  if n=0 then 1
  else simplify( 2 * a * P(n-1) * Q(n-1) + b * Q(n-1) * Q(n-1) );
  fi;
end:
for n from 0 to 4 do
  printf("P(%a) = %q\n\n",n,P(n)):
  printf("Q(%a) = %q\n\n",n,Q(n)):
end do:
#end Maple Code

These are polynomials in a,b,c and x0. Let's simplify by letting a=b=(-c)=1. Things are a bit more intersting now.

P(4) = 610 + 6032*x0 + 27960*x0^2 + 161980*x0^4 + 80640*x0^3 +
167310*x0^8 + 272272*x0^6 + 240240*x0^5 + 240240*x0^7 + x0^16 +
120*x0^14 + 3640*x0^12 + 560*x0^13 + 40040*x0^10 + 13104*x0^11 +
91520*x0^9 
 
Q(4) = 987 + 9760*x0 + 45240*x0^2 + 262080*x0^4 + 130480*x0^3 +
270270*x0^8 + 440440*x0^6 + 388752*x0^5 + 388960*x0^7 + 120*x0^14 +
5460*x0^12 + 1120*x0^13 + 64064*x0^10 + 21840*x0^11 + 148720*x0^9 +
16*x0^15 

Paul, Sam, and Carl found a nice closed form expression for P and Q.

with(combinat, fibonacci):
Fib := (n) -> fibonacci(n+1):
P1 := (n,x) -> add( binomial(2^n,k) * (Fib(2^n-k-2)) * x^k,k=0..2^n):
Q1 := (n,x) -> add( binomial(2^n,k) * (Fib(2^n-k-1)) * x^k,k=0..2^n):
for n from 0 to 4 do
  printf("P(%a) - P1(%a) = %q\n",n,n,P(n)-P1(n,x0)):
  printf("Q(%a) - Q1(%a) = %q\n",n,n,Q(n)-Q1(n,x0)):
end do:

It can be shown that those expressions satisfy the recurrance for all n iff this nice little identity holds:

{2N \choose m } F(2N-m-1) = \sum_{i=0}^m {N \choose i} {N \choose m-i} \Big( 2 F(N-i-2) + F(N-i-1) \Big) F(N-m+i-1)

I really ought to prove this. It seems to hold for all n < 300.

#begin Maple Code
with(combinat, fibonacci):
Fib := (n) -> fibonacci(n+1):
LHS := (N,m) -> binomial(2*N,m)*Fib(2*N-m-1):
RHS := (N,m) -> add(binomial(N,i)*binomial(N,(m-i))*
  (2*Fib(N-i-2)+Fib(N-i-1))*Fib(N-(m-i)-1),i=0..m):
LHS(17,7) - RHS(17,7);
#end Maple Code

BACK